PELATIHAN PEMANFAATAN YOUTUBE SEBAGAI SUMBER BELAJAR SISWA DI SDN 2 JANGKAR SITUBONDO - Zaehol Fatah; Lailatur Romadhaniyah (CV. Denasya Smart Publisher, 2026)
YouTube is no longer merely an entertainment platform; it has gradually evolved into a learning space where elementary school students seek answers to their academic assignments. However, many of them still use the platform without clear direction, often clicking on videos that appear on the homepage without a specific learning purpose. This community service activity was conducted at SDN 2 Jangkar Situbondo with the aim of introducing students to the effective use of YouTube as a learning resource rather than merely as a platform for watching games or cartoons, which often consume most of their after-school leisure time. The activity employed a descriptive qualitative approach consisting of three stages: preparation, implementation, and evaluation. These stages were supported by lectures, demonstrations, and guided hands-on practice using a projector in the classroom. The results were encouraging, as students became more aware of educational YouTube channels and gained a better understanding of strategies for searching relevant learning videos. Several students demonstrated high enthusiasm by searching for tutorial videos related to subjects such as mathematics, science, and language studies. Some even compared different educational channels to determine which explanations were easier to understand. This activity demonstrates that even simple guidance delivered within a limited time can gradually shift children's habits toward a more meaningful, productive, and purposeful use of digital media